Non-disclosure agreements and externalities from silence - Jason Sockin; Aaron Sojourner; Evan Starr (W.E. Upjohn Institute for Employment Research, 2022)
We examine how non-disclosure agreements (NDAs) influence firm reputation and the flow of labor market information by analyzing three 'NDA-narrowing' state laws that prohibited firms from using NDAs to silence workers regarding unlawful workplace conduct. We document three main results. First, these laws reduced average firm ratings by approximately 5% and increased the flow of negative information, as evidenced by workers providing more negative content in online employer reviews and a rise in work-related complaints to federal agencies. Second, these laws reduced the likelihood that workers conceal aspects of their identity when spplying negative information in online employer reviews-consistent with reduced concern about retaliation risks. Finally, we find suggestive evidence that ratings dispersion across firms increased within local labor markets, consistent with broad NDAs facilitating equilibria where firms with worse employment practices can 'pool' reputations among firms with better practices. Our results highlight how firms can use broad NDAs to preserve their reputations by silencing workers, but doing so imposes negative externalities on jobseekers who value such information and on competing employers who are less able to stand out.
Keywords: M55; K31; J58; 330; Imperfect information; Non-Disclosure Agreements; Firm Reputation; Externalities